2016
DOI: 10.1016/j.cmi.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of telbivudine and entecavir in the treatment of hepatitis B e antigen-positive patients: a prospective cohort study in China

Abstract: There are few studies directly comparing the efficacy and safety of telbivudine and entecavir. The present prospective cohort study aimed to evaluate the long-term efficacy and safety of these compounds in 196 hepatitis B e antigen (HBeAg)-positive patients with chronic hepatitis B for a median follow-up period of 172 weeks; 97 were treated with telbivudine and 99 were treated with entecavir. Patients showing suboptimal responses could also take adefovir at 24-48 weeks and all patients with viral breakthrough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
(43 reference statements)
4
11
0
Order By: Relevance
“…The Practice Guidelines recommend HBeAg seroconversion for HBeAg‐positive patients as an ideal endpoint of therapy. Our results showed that the HBeAg seroconversion rate in the LdT group was 63.5%, which was significantly higher than that in the ETV group and was consistent with other reported results …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The Practice Guidelines recommend HBeAg seroconversion for HBeAg‐positive patients as an ideal endpoint of therapy. Our results showed that the HBeAg seroconversion rate in the LdT group was 63.5%, which was significantly higher than that in the ETV group and was consistent with other reported results …”
Section: Discussionsupporting
confidence: 93%
“…A sustained suppression of viral replication and the reduction in drug resistance become critical in treating patients . Our results revealed a high HBV DNA negativity with LdT and ETV treatments, which were similar to the results reported by Zhang et al Early viral suppression has significance in predicting the long‐term outcomes of antiviral therapy and improving liver histology in patients with CHB and is consistent with the results reported by Yuen et al…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations